Analysis of Tourism Travel Trends after 2014 - BAČÍK, Radovan; MUDRÍK, Martin; ŠTEFKO, Róbert; KOT, Sebastian (Journal of Environmental Management and Tourism; Vol 7 No 1 (2016): JEMT Volume VII, Issue 1(13) Spring 2016, 2016)
This paper focuses on travel preferences of the current generation and the need for monitoring the ever-changing trends in travelling. It points out that the current generation’s travel preferences are markedly different from the preferences a few years ago. Since the present time offers people many new possibilities, it is necessary to enrich one‘s offer of these wishes. The article also emphasizes the fact that if the destination wants to attract people, it should use not only different, often unconventional communication tools, but also come up with something new that people are asking for. This paper brings an overview of the research problems and also presents a picture of the current situation within the possibilities of using modern trends in tourism.
Keywords: travel preferences; unconventional communication tools; trends in tourism